2012
DOI: 10.1103/physrevb.85.035134
|View full text |Cite
|
Sign up to set email alerts
|

Correlations in quantum spin ladders with site and bond dilution

Abstract: We investigate the effects of quenched disorder, in the form of site and bond dilution, on the physics of the S = 1/2 antiferromagnetic Heisenberg model on even-leg ladders. Site dilution is found to prune rung singlets and thus create localized moments which interact via a random, unfrustrated network of effective couplings, realizing a random-exchange Heisenberg model (REHM) in one spatial dimension. This system exhibits a power-law diverging correlation length as the temperature decreases. Contrary to previ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…This was confirmed numerically in Ref. 33 in which results on depleted two-leg ladders are consistent with an upper bound of the order of z −2 reached for very low temperatures.…”
Section: B Total Spin and Curie Constantsupporting
confidence: 80%
See 3 more Smart Citations
“…This was confirmed numerically in Ref. 33 in which results on depleted two-leg ladders are consistent with an upper bound of the order of z −2 reached for very low temperatures.…”
Section: B Total Spin and Curie Constantsupporting
confidence: 80%
“…Interpretation in that sense was proposed on the same model through the study on correlation lengths. 33 Still, we observe that the RSRG argument does capture a lowering of the α(z) curve w.r.t. the 2ξz naive expectation.…”
Section: Qmc Resultsmentioning
confidence: 67%
See 2 more Smart Citations
“…Although we show results only for the homogeneous system, we have taken the trap into account and found that our conclusions remain valid [40]. Remarkably, relatives of such unusual models exist, and are employed to understand materials, 3 He-4 He mixtures, and disorder-induced phenomena [41][42][43][44][45][46][47][48][49].…”
mentioning
confidence: 64%